Survey of The Physical Condition of U-21 Rafting Athletes at Central Java Regional Training Center - Kuat Leksono; Panji Nugroho; Asyidika Indarto (Sinar Sport Journal, 2025)
Whitewater rafting requires good physical condition to support paddling. Some components of physical condition include: abdominal muscle strength, arm muscle strength, endurance, power, and togok flexibility. The purpose of this study was to describe the components of the physical condition of whitewater rafting athletes in Cilacap Regency. This study is a quantitative descriptive study with a survey approach. The sample in this study were 12 athletes from the PELADA U-21 Central Java rafting team using a total side. Measurements used the Bleep test (cardiovascular endurance), Pull-up and Sit-up (muscle strength), V-sit and reach (flexibility), and Speed ​​​​(30 Meter run).. (Methods) Data analysis used descriptive statistics, namely Norm Reference Assessment (PAN) with the help of MS Excel to determine the test results.). (Results) The test results obtained physical conditions with the following details. In the bleep test, the average was 39.067 with a median of39,150, mode44.5, and standard deviation7.5852, with a range of values ​​between27.6-49.0. The Pull Up test shows an average10.92, median14.00, mode 0, standard deviation8,028, with a value range of 0 - 21. The Push Up Test obtained an average42.83, median43.50, mode 44, standard deviation7,433, and the value range is 30 - 58. The Sit Up Test obtained an average45.54, median42, mode 42, standard deviation11,062, and the value range is 34 - 54. In the Handgrip dynamometer test, the average obtained39.57, median35.75, mode32, standard deviation11,062, with a value range of 27 - 59. In the v-sit and reach test, the average was 57.82, the median46.50, mode46, standard deviation4,933, with a value range of 36 - 52. Finally, the 30 M Running test produced an average of5.0108, median5.14, mode 4.20, standard deviation 0.48782, and the value range is 4.20 – 5.63.